Geoenvironmental engineering and geotechnics : progress in modeling and applications : proceedings of sessions of GeoShanghai 2010, June 3-5, 2010, Shanghai, China - He, Qiang, 1972-; Shen, Shui-Long (Geotechnical special publication ;, 2010)
Geoenvironmental Engineering and Geotechnics: Progress in Modeling and Applications presents 39 papers that represent the latest developments in the application of soil, rock, and groundwater mechanics in geotechnical engineering modeling and practice, including: the relationship between geotechnical engineering and sustainability; new evidence and research into the strength and deformational behavior of soil; and recent advances in characterization and modeling of groundwater flow in geological formations of diverse geotechnical properties. This Geotechnical Special Publication examines these and other important areas of geotechnical engineering using three main categories: geoenvironmental engineering; geotechnics and seepage; and porous mechanics.